2021
DOI: 10.1186/s12864-020-07268-5
|View full text |Cite
|
Sign up to set email alerts
|

ATAC-Seq identifies regions of open chromatin in the bronchial lymph nodes of dairy calves experimentally challenged with bovine respiratory syncytial virus

Abstract: Background Bovine Respiratory Syncytial Virus (BRSV) is a cause of Bovine Respiratory Disease (BRD). DNA-based biomarkers contributing to BRD resistance are potentially present in non-protein-coding regulatory regions of the genome, which can be determined using ATAC-Seq. The objectives of this study were to: (i) identify regions of open chromatin in DNA extracted from bronchial lymph nodes (BLN) of healthy dairy calves experimentally challenged with BRSV and compare them with those from non-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Multiple predisposing environmental factors have been identified which contribute to BRDC development, but these are not present in every case and cannot be used reliably to predict cases [7,115]. Genetic polymorphisms may act as diagnostic biomarkers of susceptibility to infection with HRSV [116,117] and BRSV [118,119].…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple predisposing environmental factors have been identified which contribute to BRDC development, but these are not present in every case and cannot be used reliably to predict cases [7,115]. Genetic polymorphisms may act as diagnostic biomarkers of susceptibility to infection with HRSV [116,117] and BRSV [118,119].…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…In 2014, 116 genomic loci were identified which were associated with BRDC susceptibility [123]. A recent study identified multiple open chromatin regions in the bronchial lymph nodes of calves infected with BRSV [119]. These regions were found to be involved in Th1 and Th2 pathways, pathogen recognition and the anti-viral response [119].…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine respiratory disease (BRD) is the leading cause of morbidity, mortality and economic loss in cattle of all ages both in Ireland, and internationally [1][2][3][4][5] . The extensive use of vaccines against BRD-associated viral and bacterial pathogens has not reduced the incidence or severity of BRD in cattle.…”
Section: Introductionmentioning
confidence: 99%